MEMANFAATKAN CONDENSATE HYDROCARBON NATURAL GAS SEBAGAI FUEL GAS DENGAN PENGATURAN KONDISI OPERASI ALAT HEAT EXCHANGER - Sulardi Sulardi (INFO-TEKNIK, 2019)
One of the problems faced in operating the fuel gas system is the loss due to wasting condensate hydrocarbons from the fuel gas system surge drum. The purpose of the study was to determine the factors that cause natural gas condensation problems in the fuel drum supply surge gas and provide an overview of how to overcome the problem with the heat exchanger tool operation method. The method used in the research is the research method used with a case study approach to handling wasted condensate hydrocarbon problems and how to overcome them by maximizing the operation of heat exchanger devices. The expected results from this study are that the removal of hydrocarbon condensate can be prevented and utilized as fuel gas. With the results of this study, it is expected to be an innovation in order to adding value to value creation for the company.